ANALISA KANDUNGAN MIKROORGANISME PADA RUANG BEDAH RUMAH SAKIT UMUM BUNDA THAMRIN MEDAN TAHUN 2013 - fitri mutia sari; indra chahaya; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
The microorganism content of floor and the air in the surgery room of BundaThamrin Hospital Medan city in 2013. Hospital is a unit for complex medical servicewhere a number of people at the same time, interact each other directly or indirectlyhave the same interest with patient in hospital. There for hospital need to keep andmaintain environmental sanitation to prevent nosokomial infection. The room sanitationof hospital including : ventilation, floor and wall, lighting, clean water resource, toiletand bathroom soliet weste disposal, and cleaning procedure of floor and themicroorganism content of floor and the air in the surgery room of Bunda ThamrinHospital Medan. The research is a descriptive research which done throughobservation in the surgery room. The primary data were got directly from thelaboratory result of observation the floor and the air at the surgery room the dataanalysed in frequency table. The result of showed that based on the result ofobservations it appear that the already qualified in accordance with Kepmenkes RI No.1204 2004 ventilation, clean water resource and soliet weste disposal. Mean while thefloor and wall, lighting, toilet in the bathroom and were not appear standardrequirement. Laboratory test result found that microorganism account was 3.23 3CFU/cm2 before cleaning and 2,4 2 CFU/cm2 before cleaning and 10 CFU/cm2 aftersleaning. It is suggested to hospital management to improve the condition hospitalenvironmental sanitation appear Kepmenkes RI No. 1204 2004.Keywords : Surgery Room, Environment Sanitation, Microorganism, Floor,